ROUTE ANALYSIS LEARNING MODULE BASED ON GOOGLE EARTH ROAD CLASSIFICATION FOR GEOMATICS COURSE - Sunar Rochmadi; Bening Jannati Rupi; Nuryadin Eko Raharjo; Nur Hidayat; Wisnu Rachmad Prihadi; Rudi Nur Syamsudin (LPPM Universitas Negeri Jakarta, 2024)
Due to limited learning resources and low student grades in the Geomatics course, it is very important to carry out this research to improve the quality of special learning activities in the Geomatics course. This research aims to develop a route analysis learning module based on Google Earth Road Classification. This research uses the Thiagarajan Research and Development (R&D) model, known as 4D design. The data collection technique uses a questionnaire to reveal the validity of the product based on material experts, media experts, and user responses. The result of this research is a product development using a 4D R&D model with stages (1) defining, which refers to needs based on competency in Geomatics subjects, especially in operating the Google Earth application; (2) design, which includes four learning activities on A4 paper size and 12pt Arial font; (3) development, which was completed with validation results from material experts totaling 122 scores with an average of 4.07 (suitable); from media experts, 201 scores with an average of 4.28 (very appropriate); as well as the development stage. user feasibility results of 3666 scores with an average of 4.52 (very feasible); (4) the dissemination stage, which is carried out by distributing learning modules to lecturers in geomatics courses and uploading the products developed to Google Drive to be used as learning media. The implications of this research will provide changes to learning activities, and the existence of learning modules is expected to improve student learning outcomes.